A new species of the genus Skejotettix (Orthoptera, Tetrigidae) from Nepal - Madan Subedi (Journal of Orthoptera Research, 2023)
This paper describes a new species of Skejotetix Subedi, 2022, S. kasalo sp. nov., from the temperate forests of Bajung, Parbat, Nepal. The genus was known only from the subtropical regions of Nepal. The new species and its different life stages were observed in the natural habitat. It was found to have many colors that match perfectly with the surroundings. The genus Skejotettix was considered brachypronotal until now, but a macropronotal form was also found alongside the typical brachypronotal form in S. kasalo sp. nov. The macropronotal form is an important piece of the puzzle in determining the relationship between Skejotettix and Ergatetttix Kirby, 1914.